2007
DOI: 10.1038/sj.bjc.6603760
|View full text |Cite
|
Sign up to set email alerts
|

Number of siblings and the risk of solid tumours: a nation-wide study

Abstract: We analysed the effects of number of siblings on the risk of solid tumours using the Swedish Family-Cancer Database, including population-based information on over 11 million individuals and more than 178 000 cancer patients diagnosed between 1958 and 2004. Incidence rate ratios (RRs), estimated by Poisson regression models, were adjusted for age, sex, birth cohort, area of residence and socioeconomic status. Having eight or more siblings vs none increased the risk of stomach cancer (RR ¼ 1.83, 95% confidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 46 publications
3
13
0
Order By: Relevance
“…The reason our results differ from earlier reports is not clear and may be due to unknown or unmeasured confounding factors (eg, physical activity [35]), or the role of chance; another possibility is that our use of neighborhood controls may have resulted in over matching for certain factors (such as SES) and reduced our ability to observe differences for these factors. Larger family sizes have been associated with increased esophageal and gastric cancer risk in several previous studies [36; 37; 38]. We also observed increased UGI cancer risk among individuals with larger families, which may potentially be due to an infectious etiology enhanced by a crowded environment [39].…”
Section: Discussionsupporting
confidence: 66%
“…The reason our results differ from earlier reports is not clear and may be due to unknown or unmeasured confounding factors (eg, physical activity [35]), or the role of chance; another possibility is that our use of neighborhood controls may have resulted in over matching for certain factors (such as SES) and reduced our ability to observe differences for these factors. Larger family sizes have been associated with increased esophageal and gastric cancer risk in several previous studies [36; 37; 38]. We also observed increased UGI cancer risk among individuals with larger families, which may potentially be due to an infectious etiology enhanced by a crowded environment [39].…”
Section: Discussionsupporting
confidence: 66%
“…A large Swedish study found a risk ratio of 0.71 (95%CI: 0.62-0.82) for testicular cancer for five or more siblings versus none [81]. Some previous studies have found similar associations [69, 76, 79, 82] while others have not [35, 67, 77].…”
Section: Perinatal Risk Factorsmentioning
confidence: 99%
“…Brothers of TC patients tended to father a smaller number of children and had a lower proportion of unlike-sex twins. Recently, Altieri and Hemminki (2007) reported that having five or more siblings vs none (RR 0.71, 95% CI, 0.62-0.82) was associated with strong decreased risk of TC. prevent abortions and pregnancy-related complications (Palmlund, 1996).…”
Section: Subfertilitymentioning
confidence: 99%